Optimalisasi Peran Polri Dalam Penanganan Kelompok Kriminal Bersenjata di Papua - Sianturi, Binsar H.; Hanita, Margaretha (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2020)
Prevention and overcoming separatism is an important part of the government’s agenda in realizing a safe and peaceful Indonesia. The implementation of development in all regions of the country within the framework of the Unitary State of the Republic of Indonesia is always accompanied by comprehensive efforts to prevent and overcome separatism. One of the complicated problems that still seizes a lot of attention from the nation and state of the Republic of Indonesia until now is undeniable is the separatist movement that developed in several regions of the Republic of Indonesia (NKRI). The separatist movement in Papua has now become an issue that has not yet found a solution based on a comprehensive and dynamic strategy in the context of adjusting to developments in Papua. Various police efforts have been and continue to be carried out in order to overcome the separatism of armed criminal groups (KKB) in Papua. This study aims to examine the extent of the role of the Police in efforts to combat separatism in Papua and measures to optimize that role.